Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1542/peds.2008-0656
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Inflammation, Neonatal Sepsis, and Chronic Lung Disease: A 13-Year Hospital Cohort Study

Abstract: A fetal inflammatory response is protective for chronic lung disease. Neonatal sepsis is strongly associated with chronic lung disease, and the infecting organism is important. Coagulase-negative staphylococcal infection confers a risk for chronic lung disease similar to that of other bacteremias. Candidemia confers the greatest risk of chronic lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
131
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(147 citation statements)
references
References 27 publications
(38 reference statements)
8
131
1
4
Order By: Relevance
“…Of note, in the analysis of the groups with MV <2 wk, the risk of moderate/severe BPD was much lower in the Ureaplasma-positive infants after adjusting for the risk relating to Ureaplasma-negative infants, although it was not significant (aOR: 0.38, 95% CI: 0.010-1.58, P = 0.14). This result may partly correlate with the finding that antenatal infection per se has a protective effect against BPD (23).…”
Section: Articlessupporting
confidence: 72%
See 1 more Smart Citation
“…Of note, in the analysis of the groups with MV <2 wk, the risk of moderate/severe BPD was much lower in the Ureaplasma-positive infants after adjusting for the risk relating to Ureaplasma-negative infants, although it was not significant (aOR: 0.38, 95% CI: 0.010-1.58, P = 0.14). This result may partly correlate with the finding that antenatal infection per se has a protective effect against BPD (23).…”
Section: Articlessupporting
confidence: 72%
“…Taken together, these findings indicate that antenatal infection with either Ureaplasma species or other bacteria may inhibit alveolar epithelial repair after lung injury and remodel lung architecture, leading to developmental abnormalities. A recent clinical study reported that the placental and/or fetal inflammatory response has a protective effect against the development of BPD, presumably because of the reduced incidence of RDS and associated reduced need for MV (23). On the other hand, Marter et al reported that the risk of BPD was higher in the presence of chorioamnionitis in conjunction with MV of >7 d or postnatal sepsis (24).…”
Section: Articlesmentioning
confidence: 99%
“…In these particular studies, chorioamnionitis was associated with a decreased rather than increased risk for BPD in preterm infants. 3,49 On one hand, the effect was reversed when adjusted for mechanical ventilation, 3,50 and on the other, chorioamnionitis-exposed infants who were mechanically ventilated for more than a week were at an increased risk of BPD. 49 We have recently shown that alveolar epithelial repair mechanisms are less effective in ventilated preterm infants with chorioamnionitis, providing a potential underlying mechanism for the above mentioned association.…”
Section: Lungsmentioning
confidence: 99%
“…2 As a result, the proportion of preterm infants exposed to chorioamnionitis increases with decreasing gestational age to up to 80% below 28 weeks of gestation. 3,4 Ascending bacterial invasion of the uterine cavity is thought to be the most common route of infection, although bacteria are identified only in the minority of cases. 2 Organisms most frequently associated with chorioamnionitis are mainly of low virulence, including Ureaplasma spp.…”
Section: Introductionmentioning
confidence: 99%
“…Его причиной может быть различный спектр биопатогенов, чаще всего коа-гулазонегативные стафилококки, реже грамотрицательные палочки и гри-бы [8,11,13,17,18,20,23,28,29,32,33]. Частота ПСН обратно пропорци-ональна весу новорожденного [12].…”
unclassified